Anteseden Manajemen Laba Dan Konsekuensinya Terhadap Laporan Korporasi Berkelanjutan (CSR) - Bambang Sudaryono (Jurnal Akuntansi, 2014)
The Goal Of This Paper Is To Examine Whether Affected By Antecedents Of Earning Management And Toward Under The Term Corporate Sustainability